The increasing diversity and complexity of the RNA-binding protein repertoire in plants - Marondedze, C. (Royal Society Publishing, 2021)
Post-transcriptional regulation has far-reaching implications on the fate of RNAs. It is gaining increasing momentum as a critical component in adjusting global cellular transcript levels during development and in response to environmental stresses. In this process, RNA-binding proteins (RBPs) are indispensable chaperones that naturally bind RNA via one or multiple globular RNA-binding domains (RBDs) changing the function or fate of the bound RNAs. Despite the technical challenges faced in plants in large-scale studies, several hundreds of these RBPs have been discovered and elucidated globally over the past few years. Recent discoveries have more than doubled the number of proteins implicated in RNA interaction, including identification of RBPs lacking classical RBDs. This review will discuss these new emerging classes of RBPs, focusing on the current state of the RBP repertoire in Arabidopsis thaliana, including the diverse functional roles derived from quantitative studies implicating RBPs in abiotic stress responses. Notably, this review highlights that 836 RBPs are enriched as Arabidopsis RBPs while 1865 can be classified as candidate RBPs. The review will also outline outstanding areas within this field that require addressing to advance our understanding and potential biotechnological applications of RBPs.